Factors that influence on dividend policy - Adi Kuswanto; Ari Kharisma; - Sardiyo (Conference In Business, Accounting, And Management (CBAM), 2012)
Dividend is an interesting topic to discuss, since dividend is considered as expenses by a company, but it is an income for shareholders. Some companies regularly pay dividend, but some does not. This research aimed to investigate the factors that influence on dividend policy. Samples in this research are banking and manufacturing companies listed on the IDX (Indonesia Stock Exchange) from the years 2008-2010. The dependent variables of the study is dividend payout ratio (DPR) and the independent variables consist of insider ownership; other firm ownership; shareholder dispersion, company growth; profit margin; return on assets; return on equity; and free cash flow. We use multiple regressions to analyze the data. For sample banking companies, the results shows that factor that influence on dividend policy is ROE, but the others do not have. For sample manufacturing companies the results shows that factor that there are no factors that has influence on dividend policyKeyword: Agency Theory, Growth, Net Profit Margin, Return on Asset, Return on Equity, Dividend.Â